Fan Assisted Extraction of Volatile Carbonyl Compounds from Coffee Brews Based on the Full Evaporation Technique - Mariana S. Aguiar; André F. S. M. R. Coelho; Paulo J. Almeida; João Rodrigo Santos (Foods, 2023)
In this work, the fan assisted extraction approach is originally exploited to determine volatile compounds in liquid samples based on the full evaporation technique. The feasibility of this strategy was firstly evaluated using model solutions containing different volatile carbonyl compounds. Different media, volumes of sample, temperatures of extraction, and times of extraction were tested. Linear regressions presenting r > 0.999, intermediate precision values < 6%, and recoveries within 76–95% were attained using a period of extraction of 10 min, a volume of sample solution of 5 µL, and a temperature of extraction of 50 °C. Analyses of brewed coffees were performed. The slopes of the calibration curves obtained using aqueous model solutions and brewed coffee samples were not significantly different. These results revealed no matrix effect under the selected experimental conditions, enabling the use of the external calibration method for quantification purposes. Twenty-four volatile carbonyl compounds were identified in brewed coffee, which elucidates the sensitivity of this approach.